A life cycle cost analysis system and method - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (2016)
The present invention relates to a system for determining a building life cycle cost of comprising: a user module for acquiring from a user, a plurality of cost components including at least one initial capital costs, operation costs, maintenance and replacement costs, financial costs and salvage costs; an admin module for accessing a plurality of data of reference cost components of the building stored in a database (103); a search module for determining at least one preferred data with the cost components from the user that matching the reference cost components, wherein the search module able to determine a state of availability, accessibility, and currency and reliability of the cost components from the user; an output module for output the life cycle cost based on the preferred data determined by the search module.